Non-use Measures for Global Goods and Commons in International Law - Guggisberg, Solène, (International Law E-books Online, Collection 2026., 2025)
In a world facing major environmental crises, radical measures are increasingly called for. As a change in paradigm from our anthropocentric approach to the environment and its resources remains mostly aspirational, non-use measures present themselves as practical regulatory tools to respond to environmental degradation. This edited volume examines moratoria, bans, no-take or entry zones across regimes regulating global goods and commons. It analyses factors that have contributed to the successful adoption and implementation of non-use measures for resources in the high seas, deep seabed, atmosphere, and Antarctica. It then presents pathways for the development and adoption of further non-use measures in these areas and in outer space, before reflecting on such measures' limitations and potential.